Pendampingan Pelatihan Daur Ulang Sampah Plastik Pada Pondok Pesantren Al Hikmah Purwoasri Kediri - Nurkholida, Erna; Najahah, Najahah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Garbage is an important issue in everyday life, especially in boarding schools occupied by approximately 2500 students. The amount of waste that many every day cause many problems. In this community service is accompanied by recycling training of plastic waste to reduce the impact on earth. Assistance is carried out for 22 days with the activity is the provision of materials about waste, providing training reuse of plastic waste. Practice making various handicrafts from plastic waste. Evaluate the consolidation of results. From the evaluation results obtained the conclusion that this assistance received a positive response with all activities followed until the end. Participants produce works that can be reused such as bags, wallets and shopping bags. For the results that have been achieved in bag making obtained an average of 80 which means in terms of material variation, design and harmony of products with the category of being. Itmeans that there is still a need for future facilitation to be able to make better crafts